Opioid use for noncancer pain and risk of myocardial infarction amongst adults. (16th February 2013) - Li, L.; Setoguchi, S.; Cabral, H.; Jick, S.
Abstract Backgrounds With increasing use of opioids for chronic noncancer pain comes concern about safety of this class of drugs. Opioid‐induced hypogonadism, which could increase the risk for myocardial infarction (MI), has recently come to the attention of clinicians. To evaluate this concern we examined the association between opioid use for noncancer pain and risk of MI amongst adults. Methods We conducted a nested case‐control study using the UK General Practice Research Database. Amongst 1.7 million opioid users during 1990–2008, we identified 11 693 incident MI cases aged 18–80 years, and randomly selected up to four controls matched by age, gender, index date (date of onset symptoms or diagnosis of first‐ever MI) and general practice via risk‐set sampling. Cases and controls were required to have no cancer and no major risk factors for MI before the index date. Adjusted odds ratios (ORs) and 95% confidence intervals (CIs) were estimated from conditional logistic regression. Results Compared with nonuse, current use of opioids was associated with a 1.28‐fold (95% CI 1.19–1.37) risk of MI. Cumulative use of opioids with 11–50 (OR = 1.38, 95% CI: 1.28–1.49) or > 50 (OR = 1.25, 95% CI: 1.11–1.40) prescriptions, was also marginally associated with increased risk of MI. The risk was particularly increased in users of morphine (OR = 1.71, 95% CI: 1.09–2.68), meperidine (OR = 2.15, 95% CI: 1.24–3.74) and polytherapy (OR = 1.46, 95% CI: 1.22–1.76). Conclusions Current use of any opioids and cumulative use of 11 or more prescriptions are associated with a small increased risk for MI compared to nonuse and the risk was greater in morphine, meperidine and polytherapy users. Residual confounding, particularly confounding by indication, should be considered in interpreting our results.